Pengaruh Pendapatan Premi, Hasil Investasi, Pertumbuhan Modal dan Hasil Underwriting terhadap Pertumbuhan Aset Perusahaan Asuransi - Triana, Kadek Ria; Dewi, Gusti Ayu Ketut Rencana Sari (Jurnal Ilmiah Akuntansi dan Humanika, 2020)
This research was conducted to increase growth, income, investment, capital growth and the results of underwriting partially on the growth of assets in insurance companies listed on the Indonesia Stock Exchange in the period 2014-2018. This study uses analysis that uses numbers of variables used, therefore using quantitative. The research sample consisted of 5 companies using purposive sampling. The type of data used in this study is secondary data. Data collected from each company's financial statements. The data are then analyzed with several analyzes containing descriptive statistics, classic assumption tests and multiple regression analysis by presenting data that supports the SPSS 20. The results of research related to premiums, investment returns, capital growth and guarantee results respectively have positive and significant effects. towards asset growth in insurance companiesÂ